Avoiding laghw (nonsense, vain talk, vain actions): an initial contribution to the use of Islamic concepts in human sciences = Mengelakkan laghw (tidak masuk akal, perbincangan kosong, tindakan tidak baik): sumbangan awal penggunaan konsep Islam dalam sains manusia - Seise, Claudia (Azizah) (International Islamic University Malaysia, 2019)
This short academic note discusses the possibility of incorporating the Islamic concept of leaving laghw (nonsense, vain talk, vain actions) into the theoretical and/ or methodological frameworks of human sciences.